Adjusted comparison of daratumumab monotherapy versus real-world historical control data from the Czech Republic in heavily pretreated and highly refractory multiple myeloma patients. (4th May 2018) - Jelínek, Tomáš; Maisnar, Vladimír; Pour, Luděk; Špička, Ivan; Minařík, Jiří; Gregora, Evžen; Kessler, Petr; Sýkora, Michal; Fraňková, Hana; Adamová, Dagmar; Wróbel, Marek; Mikula, Peter; et al.
Abstract: Objectives: We conducted an adjusted comparison of progression-free survival (PFS) and overall survival (OS) for daratumumab monotherapy versus standard of care, as observed in a real-world historical cohort of heavily pretreated multiple myeloma patients from Czech Republic. Methods: Using longitudinal chart data from the Registry of Monoclonal Gammopathies (RMG) of the Czech Myeloma Group, patient-level data from the RMG was pooled with pivotal daratumumab monotherapy studies (GEN501 and SIRIUS; 16 mg/kg). Results: From the RMG database, we identified 972 treatment lines in 463 patients previously treated with both a proteasome inhibitor and an immunomodulatory drug. Treatment initiation dates for RMG patients were between March 2006 and March 2015. The most frequently used treatment regimens were lenalidomide-based regimens (33.4%), chemotherapy (18.1%), bortezomib-based regimens (13.6%), thalidomide-based regimens (8.0%), and bortezomib plus thalidomide (5.3%). Few patients were treated with carfilzomib-based regimens (2.5%) and pomalidomide-based regimens (2.4%). Median observed PFS for daratumumab and the RMG cohort was 4.0 and 5.8 months (unadjusted hazard ratio [HR], 1.14; 95% confidence interval [CI], 0.94–1.39), respectively, and unadjusted median OS was 20.1 and 11.9 months (unadjusted HR, 0.61; 95% CI, 0.48–0.78), respectively. Statistical adjustments for differences in baseline characteristics were made using patient-level data. The adjusted HRs (95% CI) for PFS and OS for daratumumab versus the RMG cohort were 0.79 (0.56–1.12; p = .192) and 0.33 (0.21–0.52; p < .001), respectively. Conclusions: Adjusted comparisons between trial data and historical cohorts can provide useful insights to clinicians and reimbursement decision makers on relative treatment efficacies in the absence of head-to-head comparison studies for daratumumab monotherapy.